Hegel in Urss. Hegelismo e ricezione di Hegel nella Russia sovietica - Finocchiaro, Valeria (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2018)
An overview of Hegel’s reception in Russia from the years of the October Revolution up to 1946. After a look at Hegel's presence in pre-revolutionary Russia (Herzen, Plechanov), I will focus on the evolution of Lenin's thought and on the Philosophical Notebooks, where Lenin overcomes the traditional distinction, established by Engels, between method and system in Hegel’s philosophy. The publication of Lenin’s Notebooks in USSR contributed to the debate between “mechanists” and “dialecticians” in the second half of the 1920s. While mechanists (Akselrod), deemed idealism as a form of superstition, dialecticians (Deborin) supported the need for a reconsideration of dialectic consistent with Lenin’s thought. n the 1930s some forms of rejection of the dialectic prevailed, whereas in 1946 Alexandrov put Hegel back at the core of the debate. Although most critics tend to dismiss Soviet philosophy as pedantic and doctrinaire, it is useful to shed light on a significant theoretical dispute that cannot be reduced to a clash between “heresy” and “orthodoxy”. Parole chiave: Hegel; Urss; Lenin; Mechanists; Dialecticians.